Der Tag von Potsdam : Der 21. März 1933 und die Errichtung der nationalsozialistischen Diktatur - Kopke, Christoph 1967- HerausgeberIn; Treß, Werner 1975- HerausgeberIn (Europäisch-jüdische Studien – Beiträge, 2013)
On 21 March 1933, the National Socialists celebrated their alliance with the old Wilhelmine elites on the "Day of Potsdam." Eighty years following 1933, the great year of upheaval, this volume more closely reexamines the historical context of the "Day of Potsdam" as a critical moment on the road to dictatorship. Nine scholarly articles reconstruct the events on the "Day of Potsdam" and analyze its importance in the culture of commemoration